Randomised clinical trial: mesalazine versus placebo in the prevention of diverticulitis recurrence. Issue 3 (23rd May 2017) - Kruis, W.; Kardalinos, V.; Eisenbach, T.; Lukas, M.; Vich, T.; Bunganic, I.; Pokrotnieks, J.; Derova, J.; Kondrackiene, J.; Safadi, R.; Tuculanu, D.; Tulassay, Z.; et al.
Summary: Background: Previous studies have reached conflicting conclusions regarding the efficacy of mesalazine in the prevention of recurrent diverticulitis. Aim: To investigate the efficacy and safety of mesalazine granules in the prevention of recurrence of diverticulitis after acute uncomplicated diverticulitis. Methods: Two phase 3, randomised, placebo‐controlled, double‐blind multicentre trials (SAG‐37 and SAG‐51) investigated mesalazine granules in patients with prior episodes (<6 months) of uncomplicated left‐sided diverticulitis. Patients were randomised to receive either 3 g mesalazine once daily or placebo (SAG‐37, n=345) or to receive either 1.5 g mesalazine once daily, 3 g once daily or placebo for 96 weeks (SAG‐51, n=330). The primary endpoint was the proportion of recurrence‐free patients during 48 weeks (SAG‐37 and SAG‐51) or 96 weeks (SAG‐51) of treatment. Results: Mesalazine did not increase the proportion of recurrence‐free patients over 48 or 96 weeks compared to placebo. In SAG‐37, the proportion of recurrence‐free patients during 48 weeks was 67.9% with mesalazine and 74.4% with placebo ( P =.226). In SAG‐51, the proportion of recurrence‐free patients over 48 weeks was 46.0% with 1.5 g mesalazine, 52.0% with 3 g mesalazine and 58.0% with placebo ( P =.860 for 3 g mesalazine vs placebo) and over 96 weeks 6.9%, 9.8% and 23.1% respectively ( P =.980 for 3 g mesalazine vs placebo). Patients with only one diverticulitis episode in the year prior to study entry had a lower recurrence risk compared to >1 episode. Safety data revealed no new adverse events. Conclusion: Mesalazine was not superior to placebo in preventing recurrence of diverticulitis. Abstract : Linked Content This article is linked to Gracie and Ford et al and Kruis and Greinwald papers. To view these articles visithttps://doi.org/10.1111/apt.14180 andhttps://doi.org/10.1111/apt.14193 .